The Routledge Companion to Journalism Ethics (Taylor & Francis, 2022)
This volume provides a comprehensive discussion of enduring and emerging challenges to ethical journalism worldwide. The collection highlights journalism practice that makes a positive contribution to people's lives, investigates the link between institutional power and ethical practices in journalism, and explores the relationship between ethical standards and journalistic practice. Chapters in the volume represent three key commitments: (1) ensuring practice informed by theory, (2) providing professional guidance to journalists, and (3) offering an expanded worldview that examines journalism ethics beyond traditional boundaries and borders. With input from over 60 expert contributors, it offers a global perspective on journalism ethics and embraces ideas from well-known and emerging journalism scholars and practitioners from around the world. The Routledge Companion to Journalism Ethics serves as a one-stop shop for journalism ethics scholars and students as well as industry practitioners and experts.
English
Keywords: Media studies; broadcasting regulation, China, ethical ideology, Ethics, hate speech, Islamic perspective, journalistic practice, Leveson, Media ethics, media representation, moral dilemmas, newsrooms, objectivity, press freedom, privacy,Religious ultra-Orthodoxy, Slow journalism, social media, social responsibility, Ubuntu, whistleblowers